PENGARUH RASIO KEUANGAN TERHADAP TINGKAT BAGI HASIL SIMPANAN MUDHARABAH BANK SYARIAH (Students' Journal of Accounting and Banking, 2012)
Islamic banks are banks whose activities have left the issue of usury. The principle of sharing a common characteristic and operating a basic foundation of Islamic financial institutions as a whole. As the population in this study is that banks are on the Islamic financial sector that have been registered in the Bank Indonesia in the period of time between the years 2006 to 2011.This study uses a non-random sampling approach is by purposive sampling, with the criteria of the Bank - Islamic Banking which has stood since the period 2006 - 2011, and Bank Syariah who have the complete data period from 2006 to 2011. The method used in this study is to use multiple regression analysis to test hypotheses using t test. Before using multiple regression analysis, conducted tests of normality, the assumption of classical test and multiple regression.Based on the results of the feasibility test model using the F test shows that the ROA, FDR, BOPO, and CAR have a significant effect on the level of savings sharing mudaraba. Adjusted R ² value in the regression model obtained for 35.8%, meaning 35.8% of the variation in the level of savings could be explained by mudharabah profitability, liquidity, efficiency ratio, the ratio of capital kecakuapan while the remaining 64.2% are explained by other variables in outside the model. While based on the hypothesis test results indicate that ROA significantly positive effect on the level of the deposit mudaraba, FDR is not a significant negative effect on the level of the deposit  udaraba, BOPO significant negative effect on the level of savings results mudaraba, and CAR is significantly negative effect on the level of deposits results mudharabahKeywords: Rate of Profit Sharing, ROA, FDR, BOPO, and CAR